Knowledge and postmodernism in historical perspective - Covington, Elizabeth; Hoyt, David; Latham, Michael; Sneider, Allison (Routledge, 1996)
Knowledge and Postmodernism in Historical Perspective offers answers to the questions, what is postmodernism? and what exactly are the characteristics of the modernism that postmodernism supercedes? This reader chronicles the western engagement with the nature of knowledge during the past four centuries while providing the historical context for the postmodernist thought of Jacques Derrida, Michel Foucault, Richard Rorty and Hayden White, and the challenges their ideas have posed to our conventional ways of thinking, writing and knowing. From the science of things to the science of human beings to the grand social theorizing associated with Adam Smith, Alexis de Tocqueville, Karl Marx and Max Weber, Knowledge and Postmodernism in Historical Perspective presents readings from the succession of thinkers whose writings helped define modern sensibilities by analyzing the human capacity for generating knowledge. The volume follows the knowledge-generating project of the modern age as it blossoms in the Enlightenment and bears fruit in the nineteenth century. The writings included reveal the linkages between science, the history of science, hermeneutics, anthropology, sociology, linguistics and philosophy from Francis Bacon's call for experimental engagement with nature in the seventeenth century to Jurgen Habermas' recent analysis of the civil society spawned by the Enlightenment.--From publisher's description.